Multi-dimensional information system model for strategic digital cities - Teixeira, Alex Volnei; Rezende, Denis Alcides (Informação & Sociedade, 2023)
Information technology and digital public services are essential components for cities providing intelligent and customized information to the citizen’s needs. As one of the multiple challenges of the strategic digital city, the researching objective is to propose a multi-dimensional information system model for cities. The research methodology is based on the Model Theory, considered the circumstantial reality, helped by the bibliographical survey and the non-participative observation. The data was collected hierarchically through the Infomapping technique, and five co-related international information system models were analyzed and compared. The result presents the multi-dimensional information system model articulated to the research constructs. The conclusion reemphasized the multi-dimensional condition of information through its dynamic nature, constituting as a strategic element for information systems, and also digital cities with the creation of a virtual social dimension, based on the new interactive relations among the multi-dimension information, citizens and the city.